Os manuais, compêndios e livros didáticos na história do ensino de Filosofia no Brasil - Monteiro, André Francisco Freire (Universidade Federal do Tocantins, 2021)
The present work is historiographical and intends to contribute to the debate on policies related to textbooks, especially in the philosophical field, as it analyzes the trajectory of school textbooks for the Teaching of Philosophy in Brazil. Based on social, economic and educational policies, it was possible to map the path that the manual for the discipline of Philosophy took, from the time of Jesuit education to the current textbook evaluation programs. The historiography of manuals and textbooks for the Teaching of Philosophy in Brazil from 1500 to 1930 was discussed, a phase in which they were the privileged supports for teaching. The debate went through the process of institutionalizing the choice of textbooks and the evaluation of school textbooks, including the period of creation of the National Textbook Commission (CNLD) and the Technical Book and Textbook Commission (COLTED), until reaching the current context, marked by the National Textbook Program (PNLD), in which it appears that school textbooks are now examined as merchandise, as another product of the cultural industry and as a profitable item. The textbook, since the beginning of the schooling process in Brazil, has always been part of the school culture and its form and content, over the years, began to be controlled via governmental assessment bodies. Currently, the Philosophy discipline has several teaching manuals available, which have been improved over time, mainly due to the inclusion of the discipline in school curricula. As a commodity, the printed textbook has been distributed in schools to students, often as the only source of reading to which they have access. We show that initiatives such as the Folhas Project, developed by the Education Department of the State of Paraná, in which the teachers themselves prepared the textbooks in a collaborative way, had a production value, per unit, much lower than that offered by the publishers. It is a textbook produced with Open Educational Resources (OER), making the book public and ready to be distributed free of charge at a specific web address, with authorization for partial or total reproduction of the work. We did a price survey and compared. From an economic point of view, the initiative proved to be a real advance, whose example should be followed by other states of the federation. Given the realization that OERs are an important alternative to the current textbook policy, as a product of this dissertation, the recommendation is: education is not a commodity and the Philosophy textbook should not be either.